The role of integration for Forensic accounting and the Bord of Supreme Audit in combating financial and administrative corruption: An exploratory study of the opinions of a sample of academics and auditors in the Kurdistan Region - Dler Mousa Ahmed; Mashod Abdulla Ahmed (QALAAI ZANIST JOURNAL, 2022)
This study aims to demonstrate the integrative role of both the forensic accounting and the Bord of Supreme Audit in the Kurdistan Region in combating the manifestations of financial and administrative corruption, which has become a serious phenomenon that the Kurdistan Region of Iraq suffers from and hinders the wheel of progress, which is a group of auditors (external auditors) and a group of professors (academics) in the universities and institutes of the Kurdistan Region of Iraq. (125) questionnaires were distributed, of which (118) valid forms were retrieved for analysis through the ready-made statistical program SPSS and the Easy Fit program, and the study reached a set of results and conclusions indicating the existence of a significant relationship between the independent variables and the dependent variable within the framework of the descriptive methodology of the study and in light of testing the study hypotheses. One of the most important findings and conclusions is the presence of financial and administrative corruption in the Kurdistan Region of Iraq, and there is an influential role for the required skills, forensic accounting techniques, and the Bord of Supreme Audit together in fighting financial and administrative corruption. In light of the results and conclusions of the study, the researcher recommended a set of recommendations, the most important of which is that the Bord of Supreme Audit in the Kurdistan Region of Iraq should seek to integrate forensic accounting in its supervisory procedures because of its advantages in combating financial and administrative corruption. As a first step, the Bord of Supreme Audit can design programs Especially for financial controllers working in the Bord of Supreme Audit the purpose of teaching them the techniques and skills of a forensic accountant